2015
DOI: 10.5761/atcs.oa.15-00089
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Occurrence and Prevention of Perioperative Stroke after Coronary Artery Bypass Grafting

Abstract: Cerebral infarction after coronary artery bypass grafting (CABG) is a serious complication and a problem that remains unsolved. We will report the onset of cerebral infarction in CABG patients in our institution, and its cause, preventive method. The subjects of this research were 761 patients who underwent on-pump isolated CABG. Preoperative, intraoperative and postoperative factors, onset of cerebral infarction and atrial fibrillation were investigated. Postoperative cerebral infarction and postoperative atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…8) In a study performed at our hospital, perioperative and postoperative β-blocker therapy had a strong influence on the occurrence of POAF, but preoperative administration of β-blockers showed no preventive effect. 6,9) The results of our two studies showed that preoperative oral administration of β-blocker could not prevent POAF probably because of a small number of patients treated with β-blocker preoperatively.…”
Section: Cause Of Atrial Fibrillation After Cardiac Surgerymentioning
confidence: 96%
See 1 more Smart Citation
“…8) In a study performed at our hospital, perioperative and postoperative β-blocker therapy had a strong influence on the occurrence of POAF, but preoperative administration of β-blockers showed no preventive effect. 6,9) The results of our two studies showed that preoperative oral administration of β-blocker could not prevent POAF probably because of a small number of patients treated with β-blocker preoperatively.…”
Section: Cause Of Atrial Fibrillation After Cardiac Surgerymentioning
confidence: 96%
“…The results of our study performed in 761 patients undergoing isolated coronary artery bypass grafting (CABG) showed that the risk factors for POAF were an age of 75 or older, chronic kidney disease, emergency surgery, cardiopulmonary bypass time >180 min, intraoperative carperitide non-use, intraoperative landiolol hydrochloride non-use, preoperative ARB non-use, preoperative calcium antagonist use, preoperative statin use, postoperative β-blocker non-use, and postoperative aldosterone blocker non-use, preoperative, perioperative and postoperative drug therapy also has a strong influence on the occurrence of POAF. 6) The results of the above-mentioned study suggested that perioperative and postoperative β-blocker use was important, and emphasized the need for β-blocker therapy to suppress pathological sympathetic hyperactivity.…”
Section: Cause Of Atrial Fibrillation After Cardiac Surgerymentioning
confidence: 99%